2017
DOI: 10.1093/jat/bkw136
|View full text |Cite
|
Sign up to set email alerts
|

Determination of ∆-9-Tetrahydrocannabinol (THC), 11-hydroxy-THC, 11-nor-9-carboxy-THC and Cannabidiol in Human Plasma using Gas Chromatography–Tandem Mass Spectrometry

Abstract: Two marijuana compounds of particular medical interest are delta-9-tetrahydrocannabinol (THC) and cannabidiol (CBD). A gas chromatography-tandem mass spectrometry (GC-MS-MS) method was developed to test for CBD, THC, hydroxy-THC (OH-THC) and carboxy-THC (COOH-THC) in human plasma. Calibrators (THC and OH-THC, 0.1 to 100; CBD, 0.25 to 100; COOH-THC, 0.5-500 ng/mL) and controls (0.3, 5 and 80 ng/mL, except COOH-THC at 1.5, 25 and 400 ng/mL) were prepared in blank matrix. Deuterated (d 3 ) internal standards were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 51 publications
1
26
0
1
Order By: Relevance
“…The average recoveries observed for THC, THC-COOH, 11-OH-THC and CBN were 74, 82, 58 and 86%, respectively. The presented method was able to achieve higher recoveries (58-86%) compared to the previously published study that reported 34-73% recoveries for cannabinoids in urine (21), while our results were found to be similar to the recoveries for cannabinoids in oral fluid (75.9-86.1%) reported by Huestis et al (22) as well as those in plasma (61.3-91.6%) reported by Andrenyak et al (20). The sample loss during the extraction process typically results from the complexity of specimen extraction procedure, and hydrophobicity of analytes; particularly, hydrophobic analytes tend to adhere to collagen of cord tissue as well as HPLC vials during the sample handling process.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…The average recoveries observed for THC, THC-COOH, 11-OH-THC and CBN were 74, 82, 58 and 86%, respectively. The presented method was able to achieve higher recoveries (58-86%) compared to the previously published study that reported 34-73% recoveries for cannabinoids in urine (21), while our results were found to be similar to the recoveries for cannabinoids in oral fluid (75.9-86.1%) reported by Huestis et al (22) as well as those in plasma (61.3-91.6%) reported by Andrenyak et al (20). The sample loss during the extraction process typically results from the complexity of specimen extraction procedure, and hydrophobicity of analytes; particularly, hydrophobic analytes tend to adhere to collagen of cord tissue as well as HPLC vials during the sample handling process.…”
Section: Resultssupporting
confidence: 75%
“…Validation experiments were carried out as previously described (20). Within-and between-run precision, accuracy, linearity, sensitivity, carryover, analytical recovery, matrix effect, hydrolysis efficiency and on-board stability of extracts were evaluated using drug-free blank umbilical cord spiked with non-deuterated and deuterated standards.…”
Section: Methods Validationmentioning
confidence: 99%
“…Blood samples were transferred into heparinized tubes and immediately centrifuged at 1,500 × g for 10 min, at 4°C. Plasma was separated and stored at −80°C until analysis, within 6 months from the collection ( Andrenyak et al, 2017 ). Plasma concentrations of CBD were measured by ultra-high-pressure liquid chromatography-mass spectrometry ( Dulaurent et al, 2014 ).…”
Section: Methodsmentioning
confidence: 99%
“…▪ gas chromatography mass spectrometry (GC-MS) detection of CBD in hair [21,22], oral [23] and plasma [24] samples; ▪ 2-dimensional-GC-MS methods for detection in oral fluid [25], plasma [26] and post mortem blood samples [27].…”
Section: Chemical Propertiesmentioning
confidence: 99%